Exploration and Research on the Mixed Teaching Mode of Basic Japanese Course under the Background of Information Technology - Wei, Yarong (Journal of physics. Conference series, 2021)
At present, the general trend of information technology development is changing from the typical technology-driven development mode to the combination of application-driven and technology-driven mode. The development of information technology brings both opportunities and challenges to the reform and innovation of foreign language teaching. This paper starts with features and types of information-based foreign language teaching, to explore the mixed teaching mode of basic Japanese course under the background of information technology. Choose a reasonable teaching platform and teaching resources according to the teaching objectives; make a good teaching design for online autonomous learning for each chapter before class; to do well in offline classroom teaching development and classroom network-assisted teaching; and supplement online learning materials effectively for students after-class learning. Pay more attention to process evaluation, multi-subject evaluation and visual data analysis and evaluation based on big data. Pay attention to the role of games in basic Japanese learning, applying information technology to the teaching of basic Japanese courses and exploring the mixed teaching mode of basic Japanese courses can improve teaching effectiveness in all directions and contribute to the overall improvement of teaching quality.